Perceptions of Masculinity and Self-Image in Adolescent and Young Adult Testicular Cancer Survivors: Implications for Romantic and Sexual Relationships - Carpentier, Melissa Y. (2010)
OBJECTIVE: To examine adolescent and young adult (AYA) testicular cancer survivors’ subjective understanding of the impact of cancer in adolescence and young adulthood, with a particular emphasis on romantic and sexual relationships. METHODS: Twenty-one AYA testicular cancer survivors, aged 18 to 34 years, were recruited from outpatient testicular cancer follow-up clinics and completed a semi-structured qualitative interview that assessed the impact of testicular cancer on their romantic and sexual relationships. RESULTS: Four themes were identified that reflected survivors’ understanding of the impact of cancer in adolescence and young adulthood: (1) embarrassment leads to delays in care-seeking, (2) testicular cancer makes you feel different from others, (3) being different from others makes you damaged goods, and (4) cancer disclosure is difficult. CONCLUSIONS: As these themes represent important components of being in a romantic/sexual relationship, either currently or in the future, AYA testicular cancer survivors would benefit from the development of tailored interventions focused on improving these relevant domains.